Entrepreneurial Education Strengthening Resilience, Societal Change and Sustainability - Seikkula-Leino, Jaana; Westerberg, Mats; Verma, Priti; Salomaa, Maria (MDPI - Multidisciplinary Digital Publishing Institute, 2022)
Working life is in a major transition. Furthermore, environmental, societal, and economic problems challenge human activities. The need to develop reliance and sustainability also through higher education is evident. It has been anticipated that emphasis on entrepreneurship competencies will be even stronger in the future. In this book, Entrepreneurial Education Strengthening Resilience, Societal Change and Sustainability, we provide insights on how to develop entrepreneurial competencies within higher education and its existing networks. First, the book guides the reader to understand how political documents steer the implementation of global goals and what could be improved. Second, we present how pedagogical solutions and models can meaningfully support the development of entrepreneurial competencies in the field of higher education. We also show the complexity of this phenomenon, thus developing a deeper understanding of this educational issue. Third, we highlight the essence of developing teacher education in this context. Fourth, we stress that entrepreneurial competencies are also needed in the working life. Lastly, we present some interesting key points for developing entrepreneurial higher education from the entrepreneurial ecosystem point of view. The book consists of 13 articles from international scientific experts in this field. Our book provides new knowledge, ideas and opportunities for creating practices to enhance the development entrepreneurial, sustainable and resilient societies. The book is targeted to researchers, policy-makers, higher education providers, stakeholders, educators and trainers.